First off, we know that the y-interecept is 2, so there is going to be a plus two in the final equation. Now with the two answers input the number 8 to see which will output 6.
6 = 1/12(8)^(2) + 2
6 = 1/12(64) + 2
6 = 64/12 + 2
6 = 16/3 + 6/3
6 does not equal 22/3
6 = 1/16(8)^(2) + 2
6 = 1/12(64) + 2
6 = 64/16 + 2
6 = 4 + 2
6 = 6
This means that y = 1/16 x^2 + 2 is the correct answer. I hope that helps!
The answer is Rotation.
Good luck!
The pair of equations:
y = x + 4
y = -2x - 2
To solve the system of equation by substitution, you would substitute one variable for it's equivalent expression. Combining the pair of equations into one equation in only one variable. The easiest way to do this is by substituting out the variable y because it is already alone on one side of the equal sign. Substitute the y in the second equation for: x+4
x+4 = -2x - 2
solve for x
x + 2x = -2 -4
3x = -6
x = -2
now use the value for x to find y by putting into either equation.
y = x + 4
y = (-2) + 4
y = 2
solution is: (-2, 2)
Answer:
It is a function.
Step-by-step explanation: Each input has only one output.